Ventricular-Assist Devices and Kidney Disease Clinical Perspectives (Springer International Publishing, 2018)
This text serves as a convenient one-stop resource on the pathogenesis, diagnosis and treatment of kidney diseases in context of advanced heart failure and presence of ventricular assist devices. Advances in managing heart failure, evidence-based practices and therapies are covered, along with the management of this unique and complex subset of patients. The book also provides insights into combined heart and kidney transplantation. Authored by leaders in nephrology, cardiology and transplantation, this book fills a critical knowledge gap in understanding and treating patients with acute or chronic dysfunction of the heart and kidneys and how one induces dysfunction in the other organ.